2005
DOI: 10.1159/000084802
|View full text |Cite
|
Sign up to set email alerts
|

Total and Free Fluoride in Toothpastes from Some Non-Established Market Economy Countries

Abstract: In 101 fluoride toothpastes, bought in local shops in Burkina Faso (n = 3), China (n = 5), Myanmar (n = 22), Nepal (n = 19), Philippines (n = 13), Syria (n = 22), Togo (n = 7) and Vietnam (n = 10), the total and free ionisable fluoride concentrations were established. The total fluoride concentration of the toothpastes was determined by gas liquid chromatography. The amount of soluble fluoride was measured after dilution in artificial saliva and treatment of the supernatants with acidic phosphatase. The free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 33 publications
2
56
0
2
Order By: Relevance
“…14 Another worrying aspect is that many so-called fluoride toothpastes, even well known brands, in developing countries do not contain the required levels of free ionisable fluoride to make them effective for caries prevention. 23 There is therefore an urgent need to work on methods by which fluoride toothpaste can be made more affordable while ensuring adequate quality control to maintain its effectiveness • Promotion of proper infection control in dental and other health settings (Fig. 4).…”
Section: How Could Dental Volunteers and Their Ngos Evolve?mentioning
confidence: 99%
“…14 Another worrying aspect is that many so-called fluoride toothpastes, even well known brands, in developing countries do not contain the required levels of free ionisable fluoride to make them effective for caries prevention. 23 There is therefore an urgent need to work on methods by which fluoride toothpaste can be made more affordable while ensuring adequate quality control to maintain its effectiveness • Promotion of proper infection control in dental and other health settings (Fig. 4).…”
Section: How Could Dental Volunteers and Their Ngos Evolve?mentioning
confidence: 99%
“…However, in order to interfere with the caries process, fluoride ions need to be soluble in their formula of the fluoride toothpastes so that they can be available for the de-and remineralization process 10) . However, other components of toothpaste including abrasives can bind to fluoride ions and interfere with their activity 17) .…”
Section: Discussionmentioning
confidence: 99%
“…However, as more number of investigations were done on fluoride toothpastes, it was found that for the toothpastes to be effective against caries, the fluorides need to be in soluble form and that the anti-caries effect could be reduced by insoluble salts formed between the free fluoride ions and the abrasives contained in the toothpastes 9,10) . Thus, it is crucial for the toothpastes to contain sufficient concentration of not only the total fluoride but also the soluble fluoride to be effective in prevention of caries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Een laatste belangrijk aspect van het verbeteren van preventieve zorg is het bevorderen van het gebruik van betaalbare en effectieve fluoridetandpasta. Veel fluoridetandpasta's in de derde wereld bevatten onvoldoende vrije fluoride ( Van Loveren et al, 2005). De aanwezigheid van vrije fluoride is een voorwaarde voor de werkzaamheid tegen cariës (Van Palenstein Helderman et al, 2004).…”
Section: Visie Van Palenstein Helderman Ea: Mondzorgvrijwilligersweunclassified